2020
DOI: 10.1109/tbme.2020.2972378
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Artifact Signals in Neck Photoplethysmography

Abstract: Objective: The neck is a very attractive measurement location for multimodal physiological monitoring, since it offers the possibility of extracting clinically relevant parameters, which cannot be obtained from other body locations, such as lung volumes. It is for this reason that obtaining PPG from the neck would be of interest. PPG signals, however, are very susceptible to artifacts which greatly compromise their quality. But the extent of this is going to depend on, the nature of the artifacts and the stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In the specific case of neck PPG, we have previously defined and characterized the most common neck PPG artifacts [14]. However, in our previous work and any previous research, there is no evidence of the development of algorithms for neck PPG artifacts classification.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the specific case of neck PPG, we have previously defined and characterized the most common neck PPG artifacts [14]. However, in our previous work and any previous research, there is no evidence of the development of algorithms for neck PPG artifacts classification.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, we recently found that neck PPG signals were more strongly modulated by the respiratory frequency than finger PPG [7]. This makes the identification of different breathing states of interest very clear, specially when having at hand the most discriminative features [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite ECG waveform, the PPG waveform is highly contingent on the measurement location [ 25 ] and is overall subject-dependent [ 1 , 18 ]. In addition, systematic noise due to motion artifacts [ 26 , 27 , 28 ] can easily distort the waveform by, for example, flattening the end of the diastolic phase, making traditional processing techniques unreliable [ 29 ]. Adaptive filtering techniques based on independent component analysis and Kalman filtering were proved unreliable in the presence of arrhythmia, as in the case of atrial fibrillation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work using neck-based PPG has been very limited, only demonstrating the feasibility of extracting signals [23,24,25] characterizing the waveform [26], and analyzing potential artefacts and exploring the optimal location [24,27]. This paper advances the state-of-the-art by presenting for the first time the a proof-of-concept of a wearable system for PPG signal acquisition, together with analysis algorithms for extraction of heart rate (HR), respiratory rate (RR), and peripheral oxygen saturation (SpO2).…”
Section: Introductionmentioning
confidence: 99%